CUSTOMS IN MERARIQ WEDDING TRADITION OF SYAFI'IYAH MADZHAB PERSPECTIVE : (CASE STUDY IN ARAB VILLAGE, AMPENAN LOMBOK) - Miftakur Rohman; Muhammad Hasyim (Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan., 2022)
This research discusses the process of customary events that occur in Lombok about marriage, namely merariq marriage or elopement that is ingrained and difficult to change, and disni discusses how to overcome this custom so that the marriage is in accordance with the shari'a that has been determined in Islam in accordance with the shafi'iyah madzhab. This study would like to reveal the marriage traditions Merariq in Kampung Arab Ampenan Lombok and Know the Practice integration of religion and marriage customs merariq in Kampung Arab Ampenan Lombok. The type of research used by the authors in this study is qualitative research. Data were collected using inteinterviews, observation, and documentation techniques that took place at the crime scene. Data analysis techniques consist of data reduction, data model and, conclusion verification. The results of this study show that this merariq marriage process has indeed become a custom and generation from the ancestors with a sacral customary process and must be carried out according to predetermined rules that do not violate predetermined norms. The result of the perspective of the madzhab shafiiyah or in the religion of marriage is sunah Rasulullah then it should be done with the conditions that have been established by Shari'a so that in the implementation of the Marriage merariq does not deviate from the shari'a and customs that have been running in the middle of the community